2003
DOI: 10.1152/japplphysiol.01189.2002
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the interpolated twitch torque for maximal and submaximal voluntary contractions

Abstract: The superimposed twitch technique is frequently used to study the degree of motor unit activation during voluntary effort. This technique is one of the preferred methods to determine the activation deficit (AD) in normal, athletic, and patient populations. One of the limitations of the superimposed twitch technique is its variability under given contractile conditions. The objective of this research was to determine the source(s) of variability in the superimposed twitch force (STF) for repeat measurements. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 28 publications
3
42
0
Order By: Relevance
“…Our results indicated that activation level played no role in explaining the bone strength. There seemed to be some variation in activation level among individuals, but evidently activation level is not a major determinative factor in force production in young adults (Merton 1954;Oskouei et al 2003;Stackhouse et al 2000). As has been shown previously, our results suggest that, in addition to variation in muscle volume, there is significant inter-individual variation in specific tension (Ikai and Fukunaga 1968;Maughan and Nimmo 1984), which also plays a role in determining the bone strength.…”
Section: Discussionsupporting
confidence: 75%
“…Our results indicated that activation level played no role in explaining the bone strength. There seemed to be some variation in activation level among individuals, but evidently activation level is not a major determinative factor in force production in young adults (Merton 1954;Oskouei et al 2003;Stackhouse et al 2000). As has been shown previously, our results suggest that, in addition to variation in muscle volume, there is significant inter-individual variation in specific tension (Ikai and Fukunaga 1968;Maughan and Nimmo 1984), which also plays a role in determining the bone strength.…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, the variability observed in the estimates of voluntary drive was solely a consequence of the physiological synaptic noise included in the model that characterizes motor unit firing behavior and that influences the summation of their force twitches. In actual empirical conditions other factors, such as the level of stimulation intensity, the number and type of stimulated motor units, or the level of voluntary input excitation, may introduce even greater variability in the estimates, as discussed by Arampatzis et al (2007), Babault (2009), Herzog (2009), Folland and Williams (2007, and Oskouei et al (2003), among others. As an example, consider that only some studies (Bilodeau 2006;McKenzie et al 1992;Schillings et al 2003;Todd et al 2003) but not others (Bigland-Ritchie et al 1978;Schillings et al 2007) have observed exercise-induced central fatigue during voluntary fatiguing contractions.…”
Section: Reliability Of Interpolated Twitch As Measure Of Voluntary Dmentioning
confidence: 99%
“…Doublet stimulation was chosen to increase the signal-to-noise ratio 2 and to decrease effects of potentiation. 26 Experimental Protocol. After a warm-up of 10 submaximal isometric extensions of increasing intensity, subjects performed one MVC for the knee extensors to determine target levels for the subsequent submaximal contractions with superimposed electrical stimulation.…”
Section: Muscle Nerve 45: 841-848 2012mentioning
confidence: 99%
“…Electromechanical delay was taken into account when voluntary torque and superimposed torque were calculated. 26 7 In addition, we calculated VA in an alternative way (VA 60-100% ) as suggested by others, 7,27 by dividing MVT over MTC 60-100% , which was obtained by extrapolation of the linear regression line fitted on the superimposed torques obtained for voluntary torques greater than 60% MVC. Figure 2A illustrates the calculation of MTC 100% and MTC 60-100% .…”
Section: Muscle Nerve 45: 841-848 2012mentioning
confidence: 99%